'Courses for Horses': designing, adapting and implementing self practice/self-reflection programmes. (29th April 2019) - Freeston, Mark H.; Thwaites, Richard; Bennett-Levy, James
Abstract: Self-Practice/Self-Reflection (SP/SR) has been proposed both as an adjunct to therapy training programmes, and also as a means for therapist development among experienced therapists. Research suggests it develops aspects of knowledge and skill that may not be addressed through other training methods. With increasing interest in SP/SR, a growing evidence base regarding both participant benefits and potential risks from SP/SR, and the development of SP/SR programmes across a range of therapeutic modalities, we argue it is timely to identify a set of principles that can guide the design, adaptation and implementation of SP/SR programmes. At this stage, there is little empirical evidence to guide trainers wishing to implement SP/SR in different contexts. Accordingly, these principles have been derived from reflection on developing, testing and implementing SP/SR programmes as well as on other training and supervisory experience. The first set of principles detailed in Section 1 draw on various theories of learning and development and frame the processes involved, the next principles speak to the content of SP/SR programmes, and the final principles address structure. Within Section 2, the principles are then considered for their practical implications. In Section 3, the sharing of what are initially private self-reflections is then considered together with some implications for SP/SR programmes, especially when there is assessment involved. We argue that SP/SR will continue to progress with well-designed standard programmes, careful implementation, thoughtful adaptation, ongoing innovation, and especially more evaluation. Key learning aims: (1) To understand the principles for designing, adapting and implementing SP/SR programmes that are drawn from theory and from the authors' experience of developing and implementing SP/SR programmes over the last 20 years. (2) To understand the possible factors that guide the processes, content and structure of SP/SR programmes. (3) To understand how best to maximize effective engagement and learning (and limit harm) when planning or implementing an SP/SR programme.